Financial constraints for investors and the speed of adaptation: Are innovators special? - Ulf von Kalckreuth (Deutsche Bundesbank, 2004)
This paper uses a large panel of survey data on German firms in the manufacturing sector to analyse the effects of financing constraints for investors in general and for innovative firms in particular. Survey data with information on financing conditions are potentially a valuable tool that avoids the Kaplan and Zingales (1997) critique on the use of cash flow sensitivities for the identification of financial constraints. Using the autumn and the spring wave of the Ifo Institute?s Investment Tests (IT) during the years 1988-1998, we create a panel with information on investment, innovation activity and financing conditions. Financial constraints affect the distribution of investment over time in a fundamental way. Following a shock, the adjustment of a constrained firm is slower and less spiky. After developing this argument theoretically building on Schworm?s (1980) model of optimal investment under financial constraints, we use it to test the empirical content of our survey data by means of an error correction model of investment activity. Our preliminary results indicate that constrained firms in fact do react more slowly, but that innovative firms are not especially affected. This supports an argument made by Bond, Harhoff and van Reenen (1999): In equilibrium, innovative activity will come from a group of firms that is self-selected on the basis of their being able to overcome the special difficulties of financing innovation.
Keywords: D21; D92; C23; 330; Financial constraints; investment; innovation; dynamic panel data models; Investition; Innovation; Verschuldungsrestriktion; Finanzierung; Schätzung; Deutschland